Sarsaparilla (Smilax Glabra Rhizome) Extract Activates Redox-Dependent ATM/ATR Pathway to Inhibit Cancer Cell Growth by S Phase Arrest, Apoptosis, and Autophagy. (17th November 2017) - She, Tiantian; Feng, Junnan; Lian, Shenyi; Li, Ruobing; Zhao, Chuanke; Song, Guoliang; Luo, Jie; Dawuti, Rouxianguli; Cai, Shaoqing; Qu, Like; Shou, Chengchao
ABSTRACT: Sarsaparilla ( Smilax Glabra Rhizome) exerts growth inhibitory effect on multiple cancer cells in vitro and in vivo, and redox-dependent persistent activation of ERK1/2 has been reported to underlie this effect. Here, we report an activation of ATM/ATR-dependent signaling pathway also as a mechanism for the cancer cell growth inhibition induced by the supernatant fraction of the water-soluble extract from sarsaparilla (SW). SW treatment (3.5 μg/μL) promoted the phosphorylations of ATM, ATR, and CHK1 in AGS and HT-29 cells. The ATM kinase inhibitor, KU55933, could reverse SW-induced ERK phosphorylation but not the reduced glutathione/oxidized glutathione (GSH/GSSG) imbalance in AGS cells. However, both the redox inhibitor glutathione (GSH) and ERK inhibitor U0126 antagonized SW-induced phosphorylations of ATM, ATR, and CHK1 in AGS cells. We further found KU55933 significantly antagonized SW-induced S phase arrest, apoptosis, autophagy and the resultant cell growth inhibition. Our results provide another molecular basis for the anticancer action of sarsaparilla.